2013
DOI: 10.18388/abp.2013_1975
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the expression of Lewis blood group antigens in glycoproteins of renal cancer tissues.

Abstract: Sialic acid and sialyl Lewis a/x are found on N-and O-glycans of many human malignant cells. Carbohydrate antigens can be used as tumor markers, and an increase of their levels in cancer cells is associated with tumor progression. The aim of this study was to assess the level of some Lewis blood group antigens on glycoproteins in tumor (cancer tissue), intermediate zone (adjacent to tumor tissue), and normal renal cortex/medulla (uninvolved by tumor). The study was performed on tissues taken from 30 patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…In our previous works we revealed similar, increasing tendencies of the expression of some specific sugar antigens, e.g. Lewis blood group antigens or MUC1 mucin (Borzym-Kluczyk & Radziejewska, 2013;Borzym-Kluczyk et al, 2015;Borzym-Kluczyk et al, 2012).…”
Section: Discussionsupporting
confidence: 63%
“…In our previous works we revealed similar, increasing tendencies of the expression of some specific sugar antigens, e.g. Lewis blood group antigens or MUC1 mucin (Borzym-Kluczyk & Radziejewska, 2013;Borzym-Kluczyk et al, 2015;Borzym-Kluczyk et al, 2012).…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, sialic acid is a component of the oligosaccharide determinant cluster of the Lewis type of sialic acid, ST3Gal-III, ST3Gal-IV, and ST3Gal-VI catalyzes the synthesis of sialylated Lewis antigens [ 51 ]. Borzym-Kluczyk et al demonstrated that the expression of sialylated Lewis antigens is increased in the tissues of RCC patients, which predicts a poor prognosis and a predisposition for lymph node metastases [ 52 ]. In clinical trials, an increasing number of studies concentrating on sialylation have proven substantial effects on the treatment of cancers in recent years.…”
Section: N-glycanmentioning
confidence: 99%